Strategi Komunikasi Yesus dengan Perempuan Samaria Menurut Yohanes 4:7-26 dan Implikasinya dalam Pengajaran Injil Kontemporer - Kumoro Adiatmo; Simon (Jurnal Ilmiah Tafsir Alkitab, 2024)
This research examines Jesus' interaction with the Samaritan woman as recorded in the John 4:7-26, focusing on Jesus' communication techniques and their relevance for contemporary evangelism and Christian teaching. In this dialogue, Jesus combines empathy and inclusivity to reach out to the woman, transcending ethnic and religious boundaries through the use of the "living water" metaphor, which teaches about true and spiritual worship. This study evaluates how Jesus listens and responds deeply to the woman's spiritual needs, integrating a profound understanding of the Messiah into the conversation, demonstrating an adaptive and personal communication approach. The analysis seeks to understand how Jesus’ approach, including the use of provocative questions and message adjustments based on the recipient's context, can be adapted in modern contexts to address a fast-paced and pluralistic society. The conclusions of this research offer insights on how the principles of Jesus' communication can guide modern evangelists and educators in their practice, suggesting strategies for more effective and sensitive communication in response to diversity in the current era.